Use of Management Accounting Information Systems in Decision Making Case Study - Nasrullah Nasrullah; Syamsuri Rahim; Ratna Sari; Muh. Abduh (Journal La Bisecoman, 2024)
This research aims to determine the usefulness of management accounting information systems in decision making in the PT PLN (Persero) UP3 North Makassar case study. Judging from the type of data, the research approach used in this research is a qualitative approach. The informants who were the data sources were the North Makassar UP3 Manager, Finance and Accounting Team Leader, and Administrative and General Staff. The results of the research are that PT PLN (Persero) UP3 North Makassar uses a management accounting information system in the form of an ERP (Enterprise Resource Planning) application which functions to provide information to each section so that it can be taken into consideration in decision making by managers of PT PLN (Persero) UP3 Makassar North.